A method for preparing porous ceramic prosthesis by combining photothermal curing
Through the combined photothermal curing preparation method, the problem of difficult preparation of porous structures in ceramic prosthesis molding is solved, and high-precision and efficient preparation of ceramic prosthesis is achieved, which enhances the stability of the implant and the strength of bone tissue binding.
Patent Information
- Application Number
- CN202411414659.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Traditional ceramic prosthesis molding technology is difficult to prepare complex porous structures, resulting in insufficient binding area and binding strength between bone implants and bone tissue. It is difficult for photocuring 3D printing to mold ceramic slurry with high solid content, dark color particles or nanoparticles. High, low efficiency.
Using photothermal curing combined preparation method, high-precision complex templates are produced through photocuring 3D printing technology, and thermal curing of ceramic slurry and decomposition of templates are carried out through gradient heating to ensure the order of the ceramic blank and the glue discharge, and the neck design Shrink the portion to reduce the effect of template decomposition on the bore structure.
The preparation of high-precision porous ceramic prosthesis is realized, which reduces cracks and warping defects, improves the appearance accuracy and stability of the blank, enhances the anchoring effect between the implant and the human body, and improves the binding strength of the bone implant.
Smart Images

Figure CN118930286B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical ceramic forming, and specifically provides a method for preparing a porous ceramic prosthesis by combining photothermal curing. Background Art
[0002] In recent years, ceramic materials have been widely used in the field of medical devices. Ceramic prostheses, alumina, zirconia, etc. have excellent mechanical properties and biocompatibility. In addition, ceramic prostheses have good antibacterial properties. However, in the molding technology of ceramic prostheses, traditional molding technologies such as gel injection molding and isostatic pressing are difficult to prepare complex porous structures, which is not conducive to increasing the bonding area and bonding strength between bone implants and bone tissues. Photocuring 3D printing is the earliest and most mature 3D printing technology. Its basic principle is to use the photocurability of photosensitive resins, project the light source through graphic programming onto the resin surface, decompose the free radical components contained in the resin, and then cause the polymerization of the photosensitive resin, so as to form a performance graphic structure at the position corresponding to the ultraviolet light. Its advantages include high precision, smooth surface of the printed object, and fast printing speed. However, some ceramic slurries containing high solid content, dark color particles or nanoparticles have low transmission depth, high surface energy of ceramic powders, easy agglomeration, irregular particle morphology, and poor fluidity, resulting in high difficulty and low efficiency in direct photocuring molding of ceramics.
[0003] CN 103553636 B discloses an engineering ceramic gel injection molding method, comprising the following steps: 1) adding mixed engineering ceramic powder and 0.8-1.5% of the total weight of the mixed engineering ceramic powder as a cross-linking agent carbomer to a solvent, mixing and ball milling for 3-5 hours to obtain a suspended stable slurry; 2) adding an initiator equivalent to 0.5-1.0% of the total weight of the mixed engineering ceramic powder to the slurry, ball milling for 7-9 minutes, and vacuum degassing for 6-8 minutes; 3) injecting into a mold for in-situ solidification of the colloid, drying, demoulding, and placing in a constant temperature oven for drying.
[0004] CN 110590369 B discloses a continuous gradient TiC porous ceramic and a template compression preparation method thereof. The porosity of the two sides of the TiC porous ceramic is 60-90% and 80-95% respectively, and the density difference of the two sides is 20%-100%, with a continuous transition in between. The preparation method is as follows: Ti powder, C powder, PVB and ethanol are prepared into slurry; a polyurethane sponge with a certain pore size is selected, cut into a trapezoid, and placed in a rectangular frame with the same width as the upper bottom size of the trapezoidal sponge, so that the trapezoidal sponge is uniformly compressed to different degrees from top to bottom. With this sponge as a template, a gradient porous ceramic body is obtained by a slurry impregnation method, and then pressureless sintering is performed to obtain the continuous gradient TiC porous ceramic of the present invention. The TiC porous ceramic prepared by the present invention has a continuous gradient structure, and the porosity of the two sides can be adjusted by selecting a sponge with an appropriate pore size, changing the ratio of the upper and lower bottoms of the trapezoidal sponge, and changing the number of slurry hanging times.
[0005] Among the above ceramic device forming methods, although the colloidal in-situ solidification forming can obtain a green body with uniform density, it is easy to generate internal stress during the liquid-solid transition process, and the internal stress will develop, inherit and mutate during the drying, debinding, sintering and machining processes. Although the porous ceramics prepared by the sacrificial sponge template method are simple to operate, highly controllable in structure and low in cost, the shape of the pores is difficult to control, and it is difficult to make high-precision porous ceramic devices.
[0006] In order to overcome the above disadvantages, the present invention performs gradient control on the decomposition temperature and curing temperature of the photosensitive resin and the thermosetting resin, thereby forming a method for preparing a porous ceramic prosthesis by combining photothermal curing. Summary of the invention
[0007] In view of the above problems, the present invention provides a method for preparing porous ceramic prostheses by combining photocuring and thermal curing. On the one hand, high-precision complex templates can be produced by photocuring 3D printing technology. On the other hand, the thermal curing of ceramic slurry, decomposition of the template and debinding of the ceramic body can be carried out in sequence by gradient heating.
[0008] The present invention provides a method for preparing a porous ceramic prosthesis by photothermal curing, comprising the following steps: S1, mixing epoxy acrylic resin, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and a photoinitiator in a certain mass ratio to obtain a photocurable resin A. S2, 3D printing the photocurable resin A using a photocuring device to obtain a template B. S3, ball milling the ceramic powder and a sintering aid, and then drying and sieving to obtain a formula powder C. S4, uniformly mixing a thermosetting resin, polyisobutylene maleic anhydride and polyethylene glycol in a certain mass ratio to obtain a mixed thermosetting resin D. S5, uniformly mixing the formula powder C and the mixed thermosetting resin D to obtain a ceramic slurry E. S6, pouring the ceramic slurry E into the template B to obtain F. S7. Raise the temperature of F to 120-150°C in a muffle furnace or a tube furnace at a heating rate of 5-10°C / min, and keep the temperature for 30 minutes to completely solidify E. Continue to raise the temperature to 250°C and keep the temperature for 2 hours, and the template B begins to decompose. Continue to raise the temperature to 400°C and keep the temperature for 2 hours, and the template B is completely decomposed. Cool with the furnace to obtain a ceramic prosthesis blank G. S8. Raise the temperature of the ceramic prosthesis blank G to 800°C and keep the temperature for 2 hours, and the mixed thermosetting resin D is completely decomposed to obtain a pure ceramic blank H. S9. Put the pure ceramic blank H into a ceramic sintering furnace for sintering to obtain a ceramic prosthesis I.
[0009] Specifically, the initial decomposition temperature of the photocurable resin A is higher than the curing temperature of the mixed thermal curable resin D, but the complete decomposition temperature thereof is lower than the initial decomposition temperature of the mixed thermal curable resin D.
[0010] Specifically, the molecular weight of the polyethylene glycol used in the present invention is 400-800, because too low a molecular weight will reduce the decomposition temperature of the mixed thermosetting resin, while too high a molecular weight will reduce the loading performance of the mixed thermosetting resin on the ceramic powder.
[0011] Compared with the prior art, the present invention has the following beneficial effects:
[0012] The present invention increases the necking part and the closed-cell structure by designing the template B, so that the necking part of F decomposes faster during the solidification and decomposition process of the template B, reducing or eliminating the influence of the decomposition of the template B on the edge quality of the pore structure of the blank G.
[0013] The formula of the thermosetting resin D provided by the present invention, the addition of polyisobutylene maleic anhydride and PEG, enables gentle and rapid debinding, and can reduce or eliminate defects such as cracks and warping.
[0014] The present invention can make the curing of slurry E, the decomposition of template B and the debinding of green body G proceed sequentially by designing the material formula of template B and the design of thermosetting resin in ceramic slurry.
[0015] The present invention designs the structure of the necked portion of the template B so that the ceramic prosthesis can be mutually anchored with the human body through the necked portion when implanted in the human body, thereby stabilizing the position of the implant. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of the external template of the ceramic prosthesis.
[0017] Figure 2 This is an enlarged schematic diagram of the necking part.
[0018] As shown in the figure: 1. Neck shrinkage part; 2. Connecting ribs; 3. Right end of the straight transition zone; 4. Left end of the straight transition zone; 5. Closed hole; 6. Right end of the arc transition zone; 7. Left end of the arc transition zone. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention clearer, various aspects of the present invention will be described in detail in conjunction with specific embodiments. These specific embodiments are only used to illustrate the present invention and do not limit the protection scope and substantive content of the present invention.
[0020] Example 1
[0021] The present invention provides a method for preparing a porous ceramic prosthesis by combining photothermal curing, and the specific preparation process includes:
[0022] S1. Mix epoxy acrylic resin, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and a photoinitiator to obtain a photocurable resin A. The mass ratio of epoxy acrylic resin, 1,6-hexanediol diacrylate and trimethylolpropane triacrylate is 6:2:2, and the photoinitiator accounts for 3% of the total mass of the photocurable resin A.
[0023] S2. Use a light-curing device to 3D print A to obtain a template B.
[0024] S3. The ceramic powder and the sintering aid were mixed and ball-milled in a mass ratio of 4:1 between the grinding balls and the powder. The mixture was ball-milled at a low speed of 150 rpm for 96 hours, and then dried through a 200-mesh sieve to obtain a formula powder C.
[0025] S4. Evenly mix the thermosetting resin, polyisobutylene maleic anhydride and polyethylene glycol in a mass ratio of 7:1:2 to obtain a mixed thermosetting resin D.
[0026] S5. Evenly mix the formula powder C and the mixed thermosetting resin D to obtain a ceramic slurry E with a solid content of 60%.
[0027] S6. Pour the ceramic slurry E into the template B to obtain F.
[0028] S7. Heat F to 120°C in a muffle furnace or a tubular furnace at a heating rate of 5-10°C / min, and keep it warm for 30 minutes to completely solidify E. Continue to heat it to 250°C and keep it warm for 2 hours. Template B begins to decompose. Continue to heat it to 400°C and keep it warm for 2 hours. Template B is completely decomposed. Cool it in the furnace to obtain a ceramic prosthesis body G.
[0029] S8. Raise the temperature of the ceramic prosthesis body G to 800° C. and keep it at this temperature for 2 hours, so that the mixed thermosetting resin D is completely decomposed to obtain a pure ceramic body H.
[0030] S9. Place the pure ceramic body H into a ceramic sintering furnace for sintering to obtain a ceramic prosthesis I.
[0031] Template B contains connecting ribs 2, which are connected to the template wall through a necking portion 1, wherein the necking portion 1 contains closed pores 5, the diameter of the straight section between the right end 3 of the straight transition zone and the left end 4 of the straight transition zone at the necking portion 1 is 0.4 mm, and the length is 1 mm; the length between the right end 6 of the arcuate transition zone and the left end 7 of the arcuate transition zone is 3 mm, the porosity of the necking portion 1 is 50%, and the diameter of the closed pore 5 is 400 μm.
[0032] Example 2
[0033] The detailed preparation process is the same as that of Example 1, except that:
[0034] The diameter of the straight line segment between the right end 3 of the straight transition zone and the left end 4 of the straight transition zone at the necking portion 1 is 0.3 mm, and the length is 0.8 mm; the length between the right end 6 of the arcuate transition zone and the left end 7 of the arcuate transition zone is 2.5 mm.
[0035] Example 3
[0036] The detailed preparation process is the same as that of Example 1, except that:
[0037] The diameter of the straight line segment between the right end 3 of the straight transition zone and the left end 4 of the straight transition zone at the necking portion 1 is 0.5 mm, and the length is 1.2 mm; the length between the right end 6 of the arcuate transition zone and the left end 7 of the arcuate transition zone is 3.5 mm.
[0038] Example 4
[0039] S1. Mix epoxy acrylate resin, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and a photoinitiator to obtain a photocurable resin A. The mass ratio of epoxy acrylate resin, 1,6-hexanediol diacrylate and trimethylolpropane triacrylate is 6:2:2, and the photoinitiator is 3% of the total mass of the photocurable resin A.
[0040] S2. Using a light-curing device to 3D print the light-curing resin A to obtain a template B.
[0041] S3. The ceramic powder and the sintering aid are mixed and ball-milled, with the mass ratio of grinding balls to powder being 4:1. The mixture is ball-milled at a low speed of 150 rpm for 96 hours, and then dried through a 200-mesh sieve to obtain formula powder C.
[0042] S4. The thermosetting resin and polyethylene glycol (polyethylene glycol 400) are uniformly mixed at a mass ratio of 7:3 to obtain a mixed thermosetting resin D.
[0043] S5. Evenly mix the formula powder C and the mixed thermosetting resin D to obtain a ceramic slurry E with a solid content of 60%.
[0044] S6. Pour the ceramic slurry E into the template B to obtain F.
[0045] S7. Raise the temperature of F to 150°C at a heating rate of 3°C / min in a muffle furnace or a tubular furnace, and keep it warm for 30 minutes to completely solidify E. Continue to raise the temperature to 250°C and keep it warm for 2 hours. Template B begins to decompose. Continue to raise the temperature to 400°C and keep it warm for 2 hours. Template B is completely decomposed. Cool with the furnace to obtain a ceramic prosthesis body G.
[0046] S8. Raise the temperature of the ceramic prosthesis body G to 800° C. and keep it at this temperature for 2 hours, so that the mixed thermosetting resin D is completely decomposed to obtain a pure ceramic body H.
[0047] S9. Place the pure ceramic body H into a ceramic sintering furnace for sintering to obtain a ceramic prosthesis I.
[0048] Template B contains connecting ribs 2, which are connected to the template wall through a necking portion 1, wherein the necking portion 1 contains closed pores 5, the diameter of the straight section between the right end 3 of the straight transition zone and the left end 4 of the straight transition zone at the necking portion 1 is 0.4 mm, and the length is 1 mm; the length between the right end 6 of the arcuate transition zone and the left end 7 of the arcuate transition zone is 3 mm, the porosity of the necking portion 1 is 60%, and the diameter of the closed pore 5 is 500 μm.
[0049] Example 5
[0050] The detailed preparation process is the same as that of Example 4, except that the porosity of the necked portion 1 is 40%, and the diameter of the closed pore 5 is 300 μm.
[0051] Example 6
[0052] The detailed preparation process is the same as that of Example 4, except that the porosity of the necked portion 1 is 60%, and the diameter of the closed pore 5 is 300 μm.
[0053] Example 7
[0054] The detailed preparation process is the same as that of Example 4, except that the porosity of the necked portion 1 is 40%, and the diameter of the closed pore 5 is 500 μm.
[0055] Example 8
[0056] S1. Mix epoxy acrylic resin, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and a photoinitiator to obtain a photocurable resin A. The mass ratio of epoxy acrylic resin, 1,6-hexanediol diacrylate and trimethylolpropane triacrylate is 5:2:3, and the photoinitiator accounts for 3% of the total mass of the resin.
[0057] S2. Using a light-curing device to 3D print the light-curing resin A to obtain a template B.
[0058] S3. The ceramic powder and the sintering aid are mixed and ball-milled, with the mass ratio of grinding balls to powder being 4:1. The mixture is ball-milled at a low speed of 150 rpm for 96 hours, and then dried through a 200-mesh sieve to obtain formula powder C.
[0059] S4. The thermosetting resin and polyethylene glycol (polyethylene glycol 400) are uniformly mixed at a mass ratio of 1:1 to obtain a mixed thermosetting resin D.
[0060] S5. Evenly mix the formula powder C and the mixed thermosetting resin D to obtain a ceramic slurry E with a solid content of 60%.
[0061] S6. Pour the ceramic slurry E into the template B to obtain F.
[0062] S7. Raise the temperature of F to 150°C in a muffle furnace or a tubular furnace at a heating rate of 5°C / min, and keep it warm for 30 minutes to completely solidify E. Continue to raise the temperature to 250°C and keep it warm for 2 hours. Template B begins to decompose. Continue to raise the temperature to 400°C and keep it warm for 2 hours. Template B is completely decomposed. Cool with the furnace to obtain a ceramic prosthesis body G.
[0063] S8. Raise the temperature of the ceramic prosthesis body G to 800° C. and keep it at this temperature for 2 hours, so that the mixed thermosetting resin D is completely decomposed to obtain a pure ceramic body H.
[0064] S9. Place the pure ceramic body H into a ceramic sintering furnace for sintering to obtain a ceramic prosthesis I.
[0065] Template B contains connecting ribs 2, which are connected to the template wall through a necking portion 1, wherein the necking portion 1 contains closed pores 5, the diameter of the straight section between the right end 3 of the straight transition zone and the left end 4 of the straight transition zone at the necking portion 1 is 0.4 mm, and the length is 1 mm; the length between the right end 6 of the arcuate transition zone and the left end 7 of the arcuate transition zone is 3 mm, the porosity of the necking portion 1 is 50%, and the diameter of the closed pore 5 is 400 μm.
[0066] Example 9
[0067] The detailed preparation process is the same as that of Example 8, with the following differences: the diameter of the straight section between the right end 3 of the straight transition zone and the left end 4 of the straight transition zone at the necking part 1 is 0.3 mm, and the length is 0.8 mm; the length between the right end 6 of the arcuate transition zone and the left end 7 of the arcuate transition zone is 2.5 mm.
[0068] Example 10
[0069] The detailed preparation process is the same as that of Example 8, with the following differences: the diameter of the straight section between the right end 3 of the straight transition zone and the left end 4 of the straight transition zone at the necking part 1 is 0.5 mm, and the length is 1.2 mm; the length between the right end 6 of the arcuate transition zone and the left end 7 of the arcuate transition zone is 3.5 mm.
[0070] Embodiment 11
[0071] S1. Mix epoxy acrylic resin, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and a photoinitiator to obtain a photocurable resin A. The mass ratio of epoxy acrylic resin, 1,6-hexanediol diacrylate and trimethylolpropane triacrylate is 3:4:3, and the photoinitiator accounts for 3% of the total mass of the resin.
[0072] S2. Using a light-curing device to 3D print the light-curing resin A to obtain a template B.
[0073] S3. The ceramic powder and the sintering aid are mixed and ball-milled, with the mass ratio of grinding balls to powder being 4:1. The mixture is ball-milled at a low speed of 150 rpm for 96 hours, and then dried through a 200-mesh sieve to obtain formula powder C.
[0074] S4. The thermosetting resin and polyethylene glycol (polyethylene glycol 400) are uniformly mixed at a mass ratio of 1:1 to obtain a mixed thermosetting resin D.
[0075] S5. Evenly mix the formula powder C and the mixed thermosetting resin D to obtain a ceramic slurry E with a solid content of 60%.
[0076] S6. Pour the ceramic slurry E into the template B to obtain F.
[0077] S7. Raise the temperature of F to 150°C in a muffle furnace or a tubular furnace at a heating rate of 5°C / min, and keep it warm for 30 minutes to completely solidify E. Continue to raise the temperature to 250°C and keep it warm for 2 hours. Template B begins to decompose. Continue to raise the temperature to 400°C and keep it warm for 2 hours. Template B is completely decomposed. Cool with the furnace to obtain a ceramic prosthesis body G.
[0078] S8. Raise the temperature of the ceramic prosthesis body G to 800° C. and keep it at this temperature for 2 hours, so that the mixed thermosetting resin D is completely decomposed to obtain a pure ceramic body H.
[0079] S9. Place the pure ceramic body H into a ceramic sintering furnace for sintering to obtain a ceramic prosthesis I.
[0080] Template B contains connecting ribs 2, which are connected to the template wall through a necking portion 1, wherein the necking portion 1 contains closed pores 5, the diameter of the straight section between the right end 3 of the straight transition zone and the left end 4 of the straight transition zone at the necking portion 1 is 0.4 mm, and the length is 1 mm; the length between the right end 6 of the arcuate transition zone and the left end 7 of the arcuate transition zone is 3 mm, the porosity of the necking portion 1 is 60%, and the diameter of the closed pore 5 is 500 μm.
[0081] Example 12
[0082] The detailed preparation process is the same as that of Example 11, except that the porosity of the necked portion 1 is 40%, and the diameter of the closed pore 5 is 300 μm.
[0083] Embodiment 13
[0084] The detailed preparation process is the same as that of Example 11, except that the porosity of the necked portion 1 is 60%, and the diameter of the closed pore 5 is 300 μm.
[0085] Embodiment 14
[0086] The detailed preparation process is the same as that of Example 11, except that the porosity of the necked portion 1 is 40%, and the diameter of the closed pore 5 is 500 μm.
[0087] Comparative Example 1
[0088] The detailed preparation process is the same as that of Example 1, with the difference that: the template B has no necking portion 1 and closed hole 5 on the connecting rib 2.
[0089] Comparative Example 2
[0090] The detailed preparation process is the same as that of Example 1, with the difference that: there is no necking portion 1 on the connecting rib 2 of template B.
[0091] Comparative Example 3
[0092] The detailed preparation process is the same as that of Example 4, with the difference that: there is no closed hole 5 on the connecting rib 2 of template B.
[0093] Comparative Example 4
[0094] The detailed preparation process is the same as that of Example 4, except that the porosity of the necked portion 1 is 10%, and the diameter of the closed pore 5 is 400 μm.
[0095] Comparative Example 5
[0096] The detailed preparation process is the same as that of Example 1, with the following differences: the porosity at the necking portion 1 is 90%, the diameter of the closed pore 5 is 500 μm, the diameter of the straight segment between the right end 3 of the straight transition zone and the left end 4 of the straight transition zone is 0.3 mm, and the length is 0.8 mm; the length between the right end 6 of the arcuate transition zone and the left end 7 of the arcuate transition zone is 2.5 mm.
[0097] Comparative Example 6
[0098] The detailed preparation process is the same as that of Example 8, with the difference being that there is no necking portion 1 and closed hole 5 on the connecting rib 2 of template B.
[0099] Comparative Example 7
[0100] The detailed preparation process is the same as that of Example 8, with the difference that: there is no necking portion 1 on the connecting rib 2 of template B.
[0101] Comparative Example 8
[0102] The detailed preparation process is the same as that of Example 8, with the difference that: there is no closed hole 5 on the connecting rib 2 of template B.
[0103] Comparative Example 9
[0104] The detailed preparation process is the same as that of Example 11, except that the porosity of the necked portion 1 is 10%, and the diameter of the closed pore 5 is 500 μm.
[0105] Comparative Example 10
[0106] The detailed preparation process is the same as that of Example 11, except that the porosity of the necked portion 1 is 90%, and the diameter of the closed pore 5 is 300 μm.
[0107] The performance obtained under different template parameters is mainly reflected in the green body morphology quality after debinding. The differences are shown in Table 1:
[0108] Table 1
[0109] Ceramic slurry thermal curing time Body G shape accuracy (with or without deformation and defects) Example 1 Faster The green body has no obvious deformation and defects Example 2 Faster The green body has no obvious deformation and defects Example 3 Faster The green body has no obvious deformation and defects Example 4 Faster The green body has no obvious deformation and defects Example 5 Faster The green body has no obvious deformation and defects Example 6 Faster The green body has no obvious deformation and defects Example 7 Faster The green body has no obvious deformation and defects Example 8 Slow The green body has no obvious deformation and defects Example 9 Slow The green body has no obvious deformation and defects Example 10 Slow The green body has no obvious deformation and defects Embodiment 11 Slow The green body has no obvious deformation and defects Example 12 Slow The green body has no obvious deformation and defects Embodiment 13 Slow The green body has no obvious deformation and defects Embodiment 14 Slow The green body has no obvious deformation and defects Comparative Example 1 Faster The shape of the blank is severely deformed Comparative Example 2 Faster There are a few cracks in the body shape Comparative Example 3 Faster There are a few cracks in the body shape Comparative Example 4 Faster There are a few cracks in the body shape Comparative Example 5 Faster The shape of the blank is severely deformed Comparative Example 6 Slow The shape of the blank is severely deformed Comparative Example 7 Slow There are a few cracks in the body shape Comparative Example 8 Slow There are a few cracks in the body shape Comparative Example 9 Slow There are a few cracks in the body shape Comparative Example 10 Slow The shape of the blank is severely deformed
[0110] It can be seen from the technical effects of Examples 1 to 14 that by reasonably designing the necking portion 1 and the closed-cell 5 structure of template B, the preparation of a ceramic prosthesis with higher precision is achieved. The technical effects embodied in Examples 1 to 10 will cause cracks, defects and other unfavorable conditions in the ceramic prosthesis blank due to the different structural parameters of template B. And the design of the necking portion of template B allows the ceramic prosthesis to be mutually anchored with the human bone tissue through the necking portion when implanted in the human body, which can stabilize the position of the implant. If the porosity of the necking portion 1 of template B is too high, such as in Example 10, its supporting effect will be greatly reduced. Template B without closed-cell 5 and necking portion 1 will cause deformation and cracking of the edge of the blank G pore structure.
[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a porous ceramic prosthesis by combining photothermal curing, characterized by: S1. Mix epoxy acrylic resin, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and a photoinitiator to obtain a photocurable resin A; S2. Use a photocuring device to perform 3D printing on the photocurable resin A to obtain a template B, wherein the template B is provided with a connecting rib, and the connecting rib is composed of a necking portion and a closed hole. The left and right sides of the middle straight line segment of the necking portion are respectively the left end of the straight transition zone and the right end of the straight transition zone, and the left and right sides of the outer side of the necking portion are respectively the left end of the arc-shaped transition zone and the right end of the arc-shaped transition zone, and the necking portion contains a closed-cell structure, and the porosity of the necking portion is 40% to 60%, and the diameter of the closed hole is 300 to 500 μm; S3, mixing ceramic powder and sintering aid, ball milling, and then drying and sieving to obtain formula powder C; S4, uniformly mixing thermosetting resin, polyisobutylene maleic anhydride and polyethylene glycol in a certain mass ratio to obtain mixed thermosetting resin D, and the initial decomposition temperature of photocurable resin A is higher than the curing temperature of mixed thermosetting resin D, but the complete decomposition temperature of photocurable resin A is lower than the initial decomposition temperature of mixed thermosetting resin D; S5, uniformly mixing formula powder C and mixed thermosetting resin D to obtain ceramic slurry E; S6, pouring ceramic slurry E into template B to obtain F; S7. Raise the temperature of F to 120-150°C at a heating rate of 5-10°C / min in a muffle furnace or a tubular furnace, and keep the temperature for 30 minutes to completely solidify the ceramic slurry E. Continue to raise the temperature to 250°C and keep the temperature for 2 hours. The template B begins to decompose. Continue to raise the temperature to 400°C and keep the temperature for 2 hours. The template B is completely decomposed and cooled with the furnace to obtain a ceramic prosthesis body G. S8. Raise the temperature of the ceramic prosthesis body G to 800°C and keep the temperature for 2 hours. The mixed thermosetting resin D is completely decomposed to obtain a pure ceramic body H. S9. Place the pure ceramic body H in a ceramic sintering furnace and sinter it to obtain a ceramic prosthesis I.
2. The method for preparing a porous ceramic prosthesis by combining photothermal curing as claimed in claim 1, characterized in that: S2 The diameter of the straight line segment between the right end of the straight line transition zone and the left end of the straight line transition zone at the necking part is 0.3-0.5 mm, and the length is 0.8-1.2 mm.
3. The method for preparing a porous ceramic prosthesis by combining photothermal curing as claimed in claim 1, characterized in that: S2 The length between the right end of the arc-shaped transition zone and the left end of the arc-shaped transition zone is 2.5 to 3.5 mm.
4. The method for preparing a porous ceramic prosthesis by combining photothermal curing as claimed in claim 1, characterized in that: The mass ratio of the thermosetting resin, polyisobutylene maleic anhydride and polyethylene glycol described in S4 is 7:1:
2.
5. The method for preparing a porous ceramic prosthesis by combining photothermal curing as claimed in claim 1, characterized in that: The molecular weight of the polyethylene glycol described in S4 is 400-800.
6. The method for preparing a porous ceramic prosthesis by combining photothermal curing as claimed in claim 1, characterized in that: The content of polyethylene glycol in the mixed thermosetting resin D described in S4 accounts for 30% to 50% of the total volume.
Citation Information
Patent Citations
A method for gel casting of engineering ceramics
CN103553636B
A continuous gradient TiC porous ceramic and its template compression preparation method
CN110590369B
Ceramic-resin composite material based on photocuring molding and preparation method thereof
CN116573951A
Water-based photo-thermal double-effect cured ceramic slurry as well as preparation method and application thereof
CN116947503A
Zirconium tungstate-based ceramic composite material based on photocuring technology and preparation method thereof
CN118359434A
